The effects of competitive plyometric training on speed, strength, and defensive skills of handball players - Kadhem, Abbas Abdulhamza (Universitas Negeri Malang, 2025)
Background: The importance of this research lies in preparing handball players with enhanced physical and skill capabilities through modern methods such as competitive plyometric training. The study was motivated by observed performance inconsistencies among Iraqi handball teams, particularly a decline in players' physical and technical execution toward the end of matches. This issue is attributed to the use of traditional training programs, which fail to develop the players’ physical fitness and technical performance adequately. Objective: This study examines the effects of competitive plyometric training on handball players' speed, strength, and defensive skills. Methods: The research was driven by the observation that many teams in the Iraqi Handball League exhibit performance decline toward the end of matches, which is attributed to inadequate physical and skill preparation under traditional training programs. An experimental design was used, involving 18 young male players from the Karbala Handball Club, divided randomly into experimental and control groups. The experimental group followed an 8-week competitive plyometric training program, while the control group continued with standard training. Result: Results showed significant improvements in the experimental group's speed-strength and defensive skills compared to the control group. Conclusion: In conclusion, competitive plyometric training effectively enhances physical and skill performance in handball players and is recommended as part of structured training programs. It is recommended that future research explore the long-term effects of competitive plyometric training across different age groups and levels of play, to determine its applicability and sustainability in improving athletic performance.